Tujuh and Sembilan Sacred Tombs Sites in Ketapang, West Kalimantan: Historical-Archaeological Studies and Receptions - Maryani; Wendi Parwanto (Journal of Islamic History and Manuscript, 2022)
This study aims to expose the history of Islam in Ketapang by referring to Tujuh and Sembilan sacred tombs and narrating the reception (in the living al-Quran) of the community on the grave and its elements (part of the Quranic text, motifs, and others). This research is field research, using a narrative-analytic model, as well as using a historical approach and the living Quran theory (on reception). The results of this study are: 1) The history of Tujuh and Sembilan sacred tombs are the tombs of pious people who spread Islam in Ketapang around the 14th century A.D. Second, the typology of people's reception in the sentence kullu nafsin dzaiqatul maut is represented in three forms of reception, namely, hermeneutical or exegesis reception, aesthetic reception, and functional reception.